Assessment of nanoparticle emission in additive manufacturing: Comparing wire and powder laser metal deposition processes. - Pernetti, Roberta; Maffia, Simone; Previtali, Barbara; Oddone, Enrico (Journal of Occupational & Environmental Hygiene, 2023)
Additive manufacturing (AM), often referred to as 3D printing, is an emerging technology with a wide range of industrial applications and process typologies. Although the release of metal nanoparticles as by-products could occur, occupational exposure limits and cogent safety standards are not currently available due to the novelty of the technology. To support the definition of benchmarks, this study aims to provide a preliminary comparison between the nanoparticle release patterns of laser metal deposition, adopting different feedstocks, namely, metal wire and metal powder. The monitored device is a university research setup, and the work presents the results of two different processes with AISI 316 L as a feedstock in powder and wired form, respectively. The monitoring confirmed the outcomes of previous studies, with a high release of nanoparticles from the powder head on the device (average 138,713 n/cm3 during printing, with maximum values exceeding 106 n/cm3). Moreover, the results show a significant concentration of nanoparticles with a wire head during the printing phase (average release of 628,156 n/cm3 with a maximum of 1,114,987 n/cm3) and pauses (average of 32,633 n/cm3 and a maximum of 733,779 n/cm3). The monitored values during pauses are particularly relevant since no personal protection equipment was used in the wire processes and the operators could access the printing room during pauses for device interventions, thus being exposed to significant nanoparticle concentrations. This study presents a preliminary evaluation of the potential exposure during laser metal deposition while implementing different technologies and provides evidence for defining effective operational safety procedures for the operators.